2019
DOI: 10.1111/are.13968
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and muscle composition response to reduced feeding levels in juvenile red swamp crayfishProcambarus clarkii(Girard, 1852)

Abstract: Overfeeding in aquaculture can lead to suboptimal growth and increased production costs. Red swamp crayfish, Procambarus clarkii, is one of the most noteworthy species cultured in China, but little information is available on the optimal feeding levels of this species, especially in ponds cultured with macrophytes. In this study, we tested the effects of five different feeding levels (20%, 40%, 60%, 80% and 100% satiation) of an artificial diet on growth performance and muscle composition of juvenile P. clarki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Purslane weed ( P. oleracea ) seems to be a promising ingredient for inclusion in diets for intensive or semi‐intensive crayfish culture, or in new and more sustainable artificial feeds, given its added values in terms of carotenoids and polyunsaturated fatty acids that are easily converted in LC‐PUFA. From this perspective, it has been recently demonstrated that natural food items can save up to 25%–50% of the artificial feed, without affecting P. clarkii growth performance and muscle composition (Jin, Jacquin, Ren, et al, 2019). Further studies are needed to define the optimal percentages of P. oleracea inclusion in fishmeal‐based aquafeeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Purslane weed ( P. oleracea ) seems to be a promising ingredient for inclusion in diets for intensive or semi‐intensive crayfish culture, or in new and more sustainable artificial feeds, given its added values in terms of carotenoids and polyunsaturated fatty acids that are easily converted in LC‐PUFA. From this perspective, it has been recently demonstrated that natural food items can save up to 25%–50% of the artificial feed, without affecting P. clarkii growth performance and muscle composition (Jin, Jacquin, Ren, et al, 2019). Further studies are needed to define the optimal percentages of P. oleracea inclusion in fishmeal‐based aquafeeds.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh vegetables are rarely selected as primary foodstuff by crayfish, as their nutritional values are not appropriate for this species, in particular at the juvenile stage. However, this is an opportunistic species, shifting to a diet based on plant biomass when potential prey is scarce (Ilhéu & Bernardo, 1993) and the presence of plants in diet could potentially bring supplementary nutrition benefits to crayfish (Jin, Jacquin, Ren, et al, 2019). Vegetable species in crayfish extensive and semi-intensive aquaculture are considered important additional items apart from artificial feeds since they may constitute a relevant integration of P. clarkii diet, without affecting growth performance (Jin, Jacquin, Ren, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the experiment, crayfish were fed twice daily (8:00 and 18:00). For each feeding practice, the experimental diets were put into a plastic pallet (30 × 15 cm), a diagram of which was described in our previous study (Jin et al, 2019). Crayfish were fed with an excess weighted diet.…”
Section: Feeding Managementmentioning
confidence: 99%
“…They were then very finely ground into a homogeneous powder (<200 μm). All samples were then placed in a 3.5 × 5 mm tip cup for δ 15 N and δ 13 C isotope analysis (Jin et al, 2019). Specifically, 3-mg samples were combusted and the gases were analysed by gas chromatography and continuous flow-mass spectrometry (MAT-253, Thermo Fisher Scientific).…”
Section: Stable Isotope Analysismentioning
confidence: 99%